Molecular identification and phylogenetic study of Toxocara canis in domestic and stray dogs from Karbala, Iraq - Bahaa Alaa Farhan AL-Daamy; Mansoor Jadaan Ali Al-khaled (Acta Scientiarum. Animal Sciences, 2024)
The ascarid nematode, Toxocara canis, which causes Toxocariasis in dogs, is a member of the Toxocaridae family and genus Toxocara, and that is accidentally infects humans. The study was conducted to investigate the presence of T. canis in dogs in Karbala, Iraq. The study extended from January to October, 2023. This project is the first of its kind in Iraq to molecularly detect the parasite in stray dogs in Karbala and to report its prevalence in domestic and stray dogs by utilizing conventional PCR and fecal flotation techniques while controlling for risk factors. One hundred (50 stray and 50 domestic) dog fecal samples were included. The findings revealed that 26 (26%) of the total dog fecal samples were tested positive using the PCR method. In details, the infection rate was 10% in domestic dogs and 42% in stray dogs. Moreover, the rate was 9.3 in adult dogs and 38.5% in puppies. The results showed that age, lifestyle, and infection rate all showed significantly (p < 0.01) correlated relationships in dogs. The correlation between T. canis infection rates and sex was not statistically significant (p > 0.01). The PCR-based sequencing of T. canis isolates indicated a high percentage of similarities with strains from different geographical regions. The study findings indicate higher rates of T. canis infection in adult and puppy stray dogs, explaining the extent of the infection among domestic dogs and stray dogs, using the latest laboratory methods for diagnosis PCR with the use of the phylogenetic tree to show the extent of similarity with species found in neighboring countries. The study findings are important by giving initial epidemiological data for future studies and control of the parasite.